2020
DOI: 10.1111/cei.13542
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting B cell tolerance and autoantibodies in seropositive and seronegative autoimmune rheumatic disease (AIRD)

Abstract: Summary Autoimmune rheumatic diseases (AIRD) are categorized seropositive or seronegative, dependent upon the presence or absence of specific autoreactive antibodies, including rheumatoid factor and anti-citrullinated protein antibodies. Autoantibody-based diagnostics have proved helpful in patient care, not only for diagnosis but also for monitoring of disease activity and prediction of therapy responsiveness. Recent work demonstrates that AIRD patients develop autoantibodies beyond those conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 118 publications
(198 reference statements)
0
8
0
1
Order By: Relevance
“…Some reports indicate that plasma cell frequencies may be increased in snAIH cases with increased frequencies of plasma cells producing IgM, IgG, and IgA, suggesting the lack of autoantibodies in snAIH, and seronegativity is a matter of timing. 9,[17][18][19] It has been proposed that early intense antigen-antibody complex formation can confound assays. Wang et al 14 found that upon further review of subjects with snAIH during a 5 to 26 months follow-up, four of 17 (23%) became ANA positive.…”
Section: Antibodies Below the Level Of Detectabilitymentioning
confidence: 99%
“…Some reports indicate that plasma cell frequencies may be increased in snAIH cases with increased frequencies of plasma cells producing IgM, IgG, and IgA, suggesting the lack of autoantibodies in snAIH, and seronegativity is a matter of timing. 9,[17][18][19] It has been proposed that early intense antigen-antibody complex formation can confound assays. Wang et al 14 found that upon further review of subjects with snAIH during a 5 to 26 months follow-up, four of 17 (23%) became ANA positive.…”
Section: Antibodies Below the Level Of Detectabilitymentioning
confidence: 99%
“…The development of autoantibodies is hypothesised to be explained by a failure of the immune system which renders it incapable of eliminating or controlling autoreactive B cells. This failure contributes to a break of B-cell tolerance, promoting the persistence of autoreactive B cells through defective central and peripheral B-cell development checkpoints [ 8 ]. In this regard, an excessive production of BAFF has been suggested to be a potential contributor to the breach of B-cell tolerance and the consequent development of autoantibodies [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have pointed out the role of BAFF in the development of autoantibodies, such as rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPAs) [ 7 , 8 , 9 , 10 ]. The presence of these autoantibodies in RA patients would imply a higher degree of inflammation during disease, which results in a more aggressive and joint-erosive condition for the patients showing higher disease activity, as well as worse prognosis owing to accelerated progression of the disease [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progressive improvement in autoantibody laboratory assays, together with the recognition of other possible autoantibody specificities beyond RF and ACPA, have led some authors to hypothesize that at least a proportion of autoantibody-negative RA is in fact incorrectly denominated seronegative [9]. Apart from non-canonical ACPAs, which can be detected in as many as 16% of ACPA-negative patients by multiplex citrullinated peptide arrays [101], the occurrence of autoantibody responses to other post-translational modified proteins is a well-known phenomenon in RA (Table 1).…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Intensive research into the etiopathogenesis of ACPA-positive RA over the last years has substantially clarified the complex interplay between genetic risk factors and environmental susceptibility resulting in dysregulated adaptive immunity with the generation of pathogenic autoantibodies [6,7]. In contrast, the genetic architecture and the predisposing factors of autoantibody-negative RA remain an area of uncertainty, and the relative contribution of innate over adaptive immune pathways has been hypothesized but not formally proven [8,9]. Although RA is currently managed the same way irrespective of the autoantibody profile, a better understanding of the pathophysiological heterogeneity of the disease would definitively improve personalized approaches more focused on specific risk factors and immune pathways.…”
Section: Introductionmentioning
confidence: 99%